La aplicación del principio de doble conforme, en el acto administrativo de la resolución del Visto Bueno - Melisa Adriana, León Aynaguano (2021)
ABSTRACT The approval is an administrative act, by which the worker or employer can allege one of the causes established in the Labor Code, in order to unilaterally terminate the employment relationship. Because it is an act issued by the public administration, it can be challenged administratively or judicially as indicated in Article 173 of the Constitution of the Republic of Ecuador. Currently it is impossible to go before the same administration and exercise the right to object to the resolution of the Approval, by virtue of what is stated in article 183 of the Labor Code, which the Labor Judge must know about the challenge of the approval. Under this background, the present investigation entitled: "The application of the principle of double compliance, in the administrative act of the resolution of the Approval", aims to determine if the principle of double agreement applied in the resolution of the Approval in order to establish compliance with legal security. To achieve this objective, a study carried out on the principle of double conformance, administrative act, and approval; The results of the investigation establish that the Labor Code restricts the application of the principle of double agreement in the resolution of approval; Despite being recognized by the Constitution of the Republic of Ecuador and international instruments, however, part of the population indicated that it fulfilled at the time of challenging before the Labor Judge, with these grounds the inadequate application of the principle of double conforming since it imposed on the parties and they are not given the possibility of choosing the means of challenge. Keywords: Approval, challenge, administrative act, principle of double conformity. Reviewed by: Mgs. Maritza Chávez Aguagallo ENGLISH PROFESSOR c.c. 0602232324